Pengaruh Pengetahuan, Kemampuan dan Pengalaman Kerja pada Kinerja Pegawai BPBD Kabupaten Gresik - Mohamad Agung Prasetyo; Heru Baskoro (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
This research aims to determine the influence of knowledge, abilities and work experience on the performance of Gresik Regency BPBD employees. The research method used is correlational with linear regression techniques to see the relationship between variables. The research sample consisted of 44 employees. The research results show that knowledge, ability and work experience have a significant influence on employee performance with regression coefficient values ​​of 0.541 for knowledge, 0.382 for ability and 0.298 for work experience. These findings indicate that these three variables contribute 61.3% to the performance of BPBD employees.